?NEW DISPERSE DYES FROM SUBSTITUTED PYRIDINES. PART-I. SYNTHESIS OF METHYL-4, 6,DmYDROXY-20xo-l-PHENYL-5-ARYLAZOPYRIDINE-3-CARBOXYLATE AND THEIR DERIVATIVES - Parveenr, Rasheeda; Ahmed, Muhammad Aleem; Husain, Shaheen A; Parveen, Shahida (Biological Sciences - PJSIR, 2001)
The reaction of methyl-a, 6, dihydroxy-2oxo, l-phenyl pyridine-3 carboxylate (iii) with diazotized aromatic amines (ii), yielded compounds (iv) showing absorption bands between ł11IX 570-590 nm, characteristic of azo dyes. An aqueous solution of (iv) having a non-ionic dispersing agent and a dye carrier at pH 5-6 and temperature 135°C and 75°C when applied to polyester and acetate fiber respectively furnished beautiful colours ranging from orange to yellow.